Impact of Additive Manufacturing on the Strategic Alignment of Business Processes in the Logistics Industry in Europe - Nadia Dalaqmeh; Wolfram Irsa (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
The logistics industry in Europe is under constant scrutiny due to the impact of digitalizing business processes and the globalization of competing markets, especially China and the USA. Therefore, the constant optimization of corporate legacy processes and, subsequently, the reduction of logistics costs play a crucial role. The constant development of innovative solutions keeps the technological edge to stay ahead of the global competition. 3D printing technology, or additive manufacturing, represents a possibility for creating innovative complex geometries, which cannot be realized with conventional subtractive manufacturing processes. Furthermore, additive manufacturing contributes to process optimization and lower logistics costs. With the appropriate strategy, the application of additive manufacturing increases customer satisfaction with new opportunities for expansion into leading business areas with higher margins. The research of the paper examines expert statements in two balanced scorecard strategies, which include (1) corresponding key performance indicators for measurement of target achievement, (2) measurement of the realization of the defined targets, and (3) possible customer applications for 3D printing technologies. These suggestions serve as a point of reference for various organizations in the logistics industry. In addition, additive manufacturing coincides with the advances in Industry 4.0 to achieve optimal results. As the industry continues to develop further, the European logistics industry has all prerequisites to prevail in a competitive global market.
Keywords: L11; O14; O33; 330; Additive Manufacturing; Digitalization; Technological Change